Pain Catastrophizing Scale for Francophone Adolescents: A Preliminary Validation. (2008) - Tremblay, Isabelle; Beaulieu, Yves; Bernier, Annie; Crombez, Geert; Laliberté, Simon; Thibault, Pascal; Velly, Ana M; Sullivan, Michael JL
Abstract : BACKGROUND: In adults, it is well known that high levels of pain catastrophizing are related to increased pain and disability as well as to heightened anxiety and depression. However, due to the lack of a measure of pain catastrophizing adapted for francophone adolescents, little is known about the role of catastrophizing in this population. OBJECTIVES: To adapt the French version of the Pain Catastrophizing Scale (PCS) and to examine the psychometric properties and factorial structure of the PCS for Francophone Adolescents (PCS-Ado). METHODS: The French version of the PCS was modified by a group of experts. The format of the questions was modified to be appropriate for adolescents aged between 12 and 18 years. To assess the psychometric properties of the PCS-Ado, 345 adolescents completed the PCS-Ado and questionnaires measuring depression, anxiety and intensity of pain. Twelve to 16 weeks later, participants completed the questionnaires again to examine the test-retest reliability of the PCS-Ado. RESULTS: Results revealed a three-factor solution similar to the original PCS. In addition, results revealed that PCS-Ado had good internal consistency (PCS-Ado total: 0.85; rumination: 0.72; magnification: 0.66; helplessness: 0.74), and high test-retest reliability (r=0.73). Finally, significant correlations among catastrophizing, depression, anxiety and pain intensity support the construct validity of the PCS-Ado. CONCLUSIONS: The results suggest that the PCS-Ado is valid and reliable with francophone adolescents. Further research is required to assess the validity of the PCS-Ado in clinical settings.